The peacock emporium - Moyes, Jojo, 1969- (New York : Penguin Books, 2019)
"Now published in the US for the first time, an early novel by the #1New York Timesbestselling author ofMe Before You, After You,andStill Me"--
"Athene Forster embraced the Sixties like few others. Nicknamed the Last Deb, she was spoiled, beautiful, and out of control. And within two years of her marriage, the rumours had begun again. Thirty-five years on, Suzanna Peacock finds refuge from her mother's shameful legacy in her shop, the Peacock Emporium. Within its magical walls she discovers not just friendship, and an escape from her troubled marriage, but the first real passion of her life. But the spectre of her mother still haunts Suzanna, setting in place a series of dramatic events. Only by confronting the past will she finally be able to face the future"--
Keywords: FICTION / Contemporary Women; FICTION / Romance / General; FICTION / Romance / Contemporary; Romance fiction